Towards a Bully-Free Nagari Through Increasing Parental Competence in the Use of Bibliotherapy Electronic Publication (E-Pub) to Increase Victim Self-Confidence - Syukur, Yarmis; Firman, Firman; Suhaili, Neviyarni; Karneli, Yeni; Sukma, Dina; Nasution, Salsabila; Kurniady, Dedy (Publikasi Pendidikan, 2025)
This service aims to improve parents' competence in using bibliotherapy based on electronic publication (E-Pub) to increase the confidence of children who are victims of bullying. The service was conducted in Kecamatan 2 x 11 Sungai Asam Enam Lingkung, Padang Pariaman Regency, West Sumatra Province, Indonesia. Data collection methods with adapted instruments. The service sample involved 23 mothers with sampling through purposive sampling technique, with the criteria of having teenage children. The approach method applied in achieving the objectives of this service is carried out through a community-based approach (bottom up). Data were collected through pretest and posttest to measure parents' knowledge related to bibliotherapy and children's self-confidence. Data analysis was conducted using the Wilcoxon rank test to compare pretest and posttest results to see the effect of bibliotherapy assistance on parental competence. The approach used is bottom-up, which involves active community participation through the steps of focus group discussion, meeting community defined needs, training and demonstration practice, brainstorming and shared benefits, small group discussion and finally whole group. The results of the service showed a significant increase in parents' knowledge regarding the use of E-Pub as a therapeutic tool, which has a positive impact on increasing the confidence of children who are victims of bullying.